Latest Trends In 3D Printed Microfluidics - Khadija Bekkay Haouari; Mustapha Ouardouz (Incertitudes et Fiabilité des Systèmes Multiphysiques)
Over the last decade, there has been a large interest in the use of 3D printing to manufacture microfluidic devices, since it has the ability to circumvent traditional fabrication techniques limitations. These include being unable to really make complex three-dimensional architectures, expensive and time-consuming processes to change device designs, and difficulty transitioning from prototyping to mass production. In this literature review, we will look at the current trends in 3D printed microfluidics, as well as recent advances and new developments in fabrication techniques, materials, and applications. Integration of 3D printing in microfluidics research has helped in the rapid prototyping of fluidic channels and structures with high complexity at an effective cost. Applications of 3D printed microfluidics are described in the areas of healthcare, diagnostics, chemical synthesis, and biotechnology. This paper also delineates the challenges and future prospects of 3D printed microfluidics, giving insight into potential research directions and technological developments.